Lublin Marcina Wrońskiego. Mała ojczyzna w retrokryminalnym entourage'u = Marcin Wroński's Lublin. Small homeland in retro entourage - Krzywicka, Ewa (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Lublin is a character of Marcin Wroński's cycle about detective Zygmunt Maciejewski, who is as important as the investigator himself. Retro crime novel - a very historical and topographic genre according to Wroński's understanding - was an ideal means to take on the mantle of the small homelands? literature. This article aims at reading Marcin Wroński's retro crime novels as a continu?ation of the private homelands' literature as well as answering the question what picture of the city we can find in his novels.
Keywords: Wroński, Marcin (1972- ); Lublin; powieść kryminalna retro; literatura małych ojczyzn; retro crime novel; small homelands' literature